Observation of mountain lee waves with MODIS NIR column water vapor. Issue 2 (30th January 2014) - Lyapustin, A.; Alexander, M. J.; Ott, L.; Molod, A.; Holben, B.; Susskind, J.; Wang, Y.
Abstract Mountain lee waves have been previously observed in data from the Moderate Resolution Imaging Spectroradiometer (MODIS) "water vapor" 6.7 µm channel which has a typical peak sensitivity at 550 hPa in the free troposphere. This paper reports the first observation of mountain waves generated by the Appalachian Mountains in the MODIS total column water vapor (CWV) product derived from near‐infrared (NIR) (0.94 µm) measurements, which indicate perturbations very close to the surface. The CWV waves are usually observed during spring and late fall or some summer days with low to moderate CWV (below ~2 cm). The observed lee waves display wavelengths from 3–4 to 15 km with an amplitude of variation often comparable to ~50–70% of the total CWV. Since the bulk of atmospheric water vapor is confined to the boundary layer, this indicates that the impact of these waves extends deep into the boundary layer, and these may be the lowest level signatures of mountain lee waves presently detected by remote sensing over the land.